Masking by vaccines in pediatric drug safety signal detection in the EudraVigilance database. Issue 11 (31st July 2018) - Dodd, Caitlin; Pacurariu, Alexandra; Osokogu, Osemeke U.; Weibel, Daniel; Ferrajolo, Carmen; Vo, Dang H.; Becker, Benedikt; Kors, Jan A.; Sturkenboom, Miriam
Abstract: Purpose: Postmarketing drug safety surveillance relies upon measures of disproportionate reporting in spontaneous reporting systems. It has been hypothesized that products or events reported frequently may "mask" signals. Methods: We analyzed the masking effect of vaccines in pediatrics in the EudraVigilance database by conducting disproportionality analysis in the full database (containing vaccine exposures) and in a restricted set (excluding vaccine exposures). We measured performance of the reporting odds ratio (ROR) in both data sets using a pediatric‐specific drug reference set and in the absence of a reference set. We assessed masking effects across age groups and conducted a classification tree (CART) analysis. Results: Removal of vaccines decreased the ROR values both in negative and positive controls. Exceptions were drug‐event combinations including outcomes frequent in vaccine reports. When restricted to positive control associations, removal of vaccine‐related events resulted in increased ROR values for events commonly reported following vaccination. For events rarely associated with vaccination, ROR values decreased for all age groups, especially infants. Analysis in the absence of a reference set showed decrease in ROR following vaccine removal and CART revealed that change in ROR with vaccine removal depended upon age and proportion of reports including a vaccine. Conclusions: Removal of vaccines for signal detection in a pediatric population has an impact on ROR, dependent upon the reporting frequency of the event of interest in combination with vaccines. We recommend stratification by age and removal of vaccine exposures if the investigated adverse drug reactions include those typically reported in association with vaccines for the age strata.